ANALISIS SENTIMEN KEPALA DAERAH TERPILIH JELANG DAN PASCA PELANTIKAN RESMI SEBAGAI PEMIMPIN DAERAH TERPILIH PADA KONTESTASI PEMILIHAN KEPALA DAERAH 2020 - Ratnasari, Eny (Universitas Islam Syekh Yusuf, 2021)
The participation of Bobby Nasution and Gibran Rakabuming Raka in the 2020 Regional Head Election contestation drew various reactions from the public. There are pros, some are cons. Researchers found that everything in accordance with Bobby Nasution and Gibran Rakabuming Raka will always be linked to the President Joko Widodo. President Joko Widodo is said to have built dynastic politics with the participation of his son-in-law and eldest son. After the contestation was over and it turned out that Bobby Nasution and Gibran Rakabuming Raka won in their respective constituencies, it further increased their conversation and news. Researchers monitored opinions before and after the official inauguration of Bobby Nasution as Mayor of Medan and Gibran Rakabuming Raka as Mayor of Surakarta. By using the netnography method, researchers conducted monitoring with the help of the Brand24 media monitoring tools from February 18 to February 27, 2021. The results showed that more of their news and opinions in the digital realm had positive sentiments. However, researchers also monitored â€œPolitik Dinastiâ€ keywords. The results show that negative sentiment is higher than positive sentiment. Opinions related to dynastic politics were dominated by public tweets about the election of Bobby and Gibran, not forgetting to link them to President Joko Widodo.This research on public opinion can be an evaluation for Bobby and Gibran's communication team in conducting political branding. The political communication strategy of Bobby and Gibran must be better maintained because their every move will always be associated with President Joko Widodo.